Clinical Manual for the Psychiatric Interview of Children and Adolescents - Cepeda, Claudio (American Psychiatric Publishing, 2016)
Clinical vignettes illustrate important concepts and techniques, providing a real-world component that readers will find both fascinating and instructive, and the key points at the end of each chapter and numerous quick-reference tables facilitate consolidation of learning.